SEMA5A-PLXNB3 Axis Promotes PDAC Liver Metastasis Outgrowth through Enhancing the Warburg Effect - Kun Wang; Min He; Xin Fan; Jian Zhou; Jian Yang; Lin Wang; Zhihong Zhao; Chun Dai; Zixiang Zhang (Journal of Immunology Research)
Patients bearing liver metastasis of pancreatic adeno carcinoma (PDAC) suffer from poor prognosis due to its short duration and high mortality. Complex tumor microenvironment (TME) exists in liver metastatic niches, and tumor-associated macrophages (TAMs) have play vital roles in metastasis generation and outgrowth. We have discovered that M2 type TAM-derived SEMA5A could bind to its tumor cell-expressed receptor PLXNB3 to promote tumor cell proliferation and outgrowth. We utilized liver metastasis samples of PDAC patients, intrasplenic injection mouse models, and KrasG12D/Trp53R172H/Pdx1-Cre (KPC) mouse models for in vivo study. In mechanism investigation, we have discovered that SEMA5A-PLXNB3 axis could achieve tumor cell proliferation and survival via enhancing aerobic glycolysis termed as the Warburg effects. Targeting this axis may be a potential therapeutic approach for PDAC patients with unresectable liver metastasis.